Penerapan Sanksi Pidana terhadap Pelaku Judi Online Berdasarkan Undang-Undang Informasi dan Transaksi Elektronik di Kota Denpasar - Rasman, Rasman; Hutauruk, Appe; Jaya, Setia (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This research aims to analyze the application of criminal sanctions against online gambling perpetrators based on the Electronic Information and Transactions Law (UU ITE) in the jurisdiction of the Denpasar Police (Polresta Denpasar). This normative-empirical legal research uses statutory and conceptual approaches. Data was collected through interviews with law enforcement officials and analysis of primary and secondary legal materials. The findings indicate that the proliferation of online gambling in Denpasar is driven by a confluence of economic pressures, technological accessibility, psychological addiction, social normalization, and weaknesses in supervision and law enforcement. In response, Polresta Denpasar implements a holistic strategy combining repressive, preventive, and collaborative measures. Repressive efforts focus on applying Article 27 paragraph (2) of the UU ITE, although challenges persist in reaching overseas operators and limited digital forensic capacity. Preventive actions involve public education on the dangers of gambling and the promotion of local cultural values. Collaborative synergy is established with institutions like the Ministry of Communication and Informatics (Kominfo) for site blocking and the Financial Transaction Reports and Analysis Centre (PPATK) for financial flow tracking. The study concludes that effective eradication requires an integrated approach beyond mere law enforcement, addressing root causes such as economic inequality and the dynamic nature of cybercrime